KEPEDULIAN SOSIAL JOHN WESLEY DAN APLIKASINYA BAGI GEREJA-GEREJA DI INDONESIA KHUSUSNYA GEREJA METHODIST INDONESIA - Manimpan Hutasoit (Universitas Methodist Indonesia, 2024)
John Wesley’s doctrine about sanctification is biblical. This claim has been done research through analysis of dogmatic-theology. First it must be clear, and than continued to the basic impact of this doctrine toward social transformation. Understanding the impact of sanctification to social transformation would not be separated from its implications and the social context of John Wesley in that time. John Wesley’s sanctification doctrine is a very clear implications for the social transformation movement. There are implications of “inner holiness” (Love God) toward the “outer holiness” (love for follow human beings). The basic of John Wesley’s sanctification doctrine is through two-way relationship “love”. John Wesley’s sanctification doctrine which implicated to the social transformation movement is very relevant to the John Wesley’s context in that time, which in British, there was bad social background, bad economic and political and very weak spiritual. John Wesley’s doctrine is also very relevant to the social transformation movement in Indonesia, which at this time in such the contexts of property, suffering, injustice and others. Methodist church of Indonesia, in the matter of this does not need to seek a theory or another tradition of the church in order to dynamicize the church’s community to achieve common prosperity. If John Wesley said: “The World is my Parish” then it also meant Indonesia.